1991
DOI: 10.1007/bf00190015
|View full text |Cite
|
Sign up to set email alerts
|

Transpiration efficiency in crops of semi-dwarf and standard-height sunflower

Abstract: This paper compares transpiration efficiency (TE c = shoot biomass corrected by seed oil-synthesis cost/ transpiration per unit vapour pressure deficit) of standard-height and semi-dwarf sunflower (Helianthus annuus L.) crops. Three irrigation regimes that differed in timing and amount of irrigation were applied. Transpiration was calculated as the difference between evapotranspiration (assessed by hydrological balance) and soil evaporation (measured using evaporimeters). Irrigation treatments and irrigation x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
18
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 25 publications
6
18
0
Order By: Relevance
“…Close associations between RUE and WUE were reported for sunflower and spring wheat (Sadras et al, 1991;Caviglia and Sadras, 2001). The relationships in Fig.…”
Section: Resource Productivity Capture and Use Efficiencies By Sole supporting
confidence: 60%
See 1 more Smart Citation
“…Close associations between RUE and WUE were reported for sunflower and spring wheat (Sadras et al, 1991;Caviglia and Sadras, 2001). The relationships in Fig.…”
Section: Resource Productivity Capture and Use Efficiencies By Sole supporting
confidence: 60%
“…In single crops, water use efficiency (WUE DM ) is directly related to radiation use efficiency (RUE DM ) as affected by genotype and ontogeny in sunflower (Heliantus annuus L., Sadras et al, 1991) and nitrogen nutrition in wheat (Caviglia and Sadras, 2001). Key physiological and agronomic aspects of wheat-soybean double cropping and its sole crop components were widely investigated Sadras, 1999, 2002;Calviño et al, , 2003a.…”
Section: Introductionmentioning
confidence: 99%
“…In specify, the simultaneous impact of deficit irrigation in water consumption and radiation interception mainly in treatment D 4 (pluvial = without irrigation) was more important in the first and second experiment than that in third experiment. If we took the entire three hypotheses detailed in Figure 1, 2 and 3, it can conclude that deficit irrigation presented an imperative consequence in the relation between PAR abs and water consumption.Our results are in agreement with this of Sadras et al, (1991) and Caviglia and Sadras, (2001). The later authors found significant relations between radiation use efficiency and water use efficiency for sunflower and spring wheat.…”
Section: Discussionsupporting
confidence: 93%
“…This trait was likely to be associated with the highest total tuber sink strength in this cultivar. A positive association between organ sink size (analogous to sink strength), photosynthesis, and RUE has been shown for wheat (Triticum aestivum L.) (Blum et al, 1988) and sunflower (Helianthus annuus L.) (Sadras et al, 1991). Similar source-sink interactions have also been suggested for potato (Schapendonk et al, 1995;Tekalign and Hammes, 2005a).…”
Section: Discussionmentioning
confidence: 52%